Prognostic Value of Right Ventricular Echocardiography on Mortality in Intermediate-Risk Hispanic Patients with Acute Pulmonary Embolism - Kothari, Aditi; Dwivedi, Alok K.; Mukherjee, Debabrata; Rajachandran, Manu; Nickel, Nils P. (International Journal of Angiology, 2025)
There is an underrepresentation of Hispanic patients in studies examining right ventricular (RV) function in acute pulmonary embolism (PE). Although the prognostic value of RV dysfunction in acute PE is well established, there is no generalized definition of RV dysfunction. In this study, our aim was to identify echocardiographic parameters that predict short-term mortality in Hispanic patients with intermediate-risk acute PE. This study aimed to determine clinical and echocardiographic predictors of mortality in Hispanic patients with intermediate-risk PE. We retrospectively studied a cohort of Hispanic patients with acute PE diagnosed on computed tomography angiography and classified as intermediate-risk based on either imaging findings or biomarker elevation. We identified 419 patients. The mean age was 58, and 53% were females. Forty (9.5%) patients died during the 30-day follow-up. Non-survivors had a higher Pulmonary Embolism Severity Index (PESI) score (101 ± 19.4, p < 0.001), a higher incidence of diabetes, chronic kidney disease, end-stage renal disease, malignancy, and previous history of venous thromboembolism. On echocardiogram, non-survivors had an increased right ventricular end-diastolic area (32.7 ± 9 cm2), higher right ventricular to left ventricular ratio (RV/LV, 0.75 ± 0.15), elevated right ventricular systolic pressure (RVSP, 42.4 ± 8.24), reduced right ventricular fractional area change (RVFAC, 24.03 ± 7.6), and reduced lateral tricuspid annular peak systolic velocity (TR max Vel S′, 9.39 ± 2.2). In Hispanic patients with acute intermediate-risk PE, increased RV afterload (RVSP), RV dilation (RVDa, RV/LV ratio), and reduced RV systolic function (tricuspid annular plane systolic excursion, S′, RVFAC) are the most important predictors of poor short-term outcome.
Keywords: pulmonary embolism; echocardiography; right ventricular dysfunction; right ventricle; venous thromboembolism; PESI; intermediate-risk PE